GUIDELINES FOR ENHANCING THE QUALITY OF EDUCATION IN HUMAN RESOURCES OF YUYING VOCATIONAL COLLEGEIN ZHEJIANG PROVINCE PEOPLE'S REPUBLIC OF CHINA - Ming, Wang; Dulayataweesit, Nonatee; Suteeniran, Niran; Setkajorn, Sarayut; Wimuttipanya, Jittawisut (Journal of MCU Nakhondhat, 2023)
The purpose of study on 1) To study the enhancement of education quality in human resources of Yuying Vocational College in Zhejiang Province. People's Republic of China 2) To assess the characteristics of the guidelines for enhancing the quality of education in human resources. Of Yuying Vocational College in Zhejiang Province People's Republic of China 3) To study the guidelines for enhancing the quality of education in human resources of Yuying Vocational College in ZhejiangProvince. People's Republic of China were included 5 following aspects: 1) Management and policy 2) Management 3) Personnel 4) Resources and support 5) Organizational culture. The research population was Yuying Vocational College in Zhejiang Province, People's Republic of China. The samples used in this study were executives and full-time teachers. Yuying Vocational College in Zhejiang Province, China By specific random sampling, total of 201 people. The research results showed that the guidelines for enhancing the quality of education in human resources of Yuying Vocational College in Zhejiang Province People's Republic of China Opportunities are encouraged for personnel to participate in the policy formulation of educational institutes. There is a policy that is consistent with the direction of educational institute development. Executive Support and facilitating personnel to perform quality assurance work Management encourages teamwork. Able to plan appropriate use of various resources and encourage the creation of good values in the workplace It supports creative operations that can be managed effectively. Meet the objectives of the educational institution that has been set. and personnel are happy to work.